A Gain-of-Function Mutation in Nav1.6 in a Case of Trigeminal Neuralgia - Brian S Tanaka; Peng Zhao; Fadia B Dib-Hajj; Valerie Morisset; Simon Tate; Stephen G Waxman; Sulayman D Dib-Hajj (BMC, 2016)
Abstract Idiopathic trigeminal neuralgia (TN) is a debilitating pain disorder characterized by episodic unilateral facial pain along the territory of branches of the trigeminal nerve. Human pain disorders, but not TN, have been linked to gain-of-function mutations in peripheral voltage-gated sodium channels (NaV1.7, NaV1.8 and NaV1.9). Gain-of-function mutations in NaV1.6, which is expressed in myelinated and unmyelinated central nervous system (CNS) and peripheral nervous system neurons and supports neuronal high-frequency firing, have been linked to epilepsy but not to pain. Here, we describe an individual who presented with evoked and spontaneous paroxysmal unilateral facial pain and carried a diagnosis of TN. Magnetic resonance imaging showed unilateral neurovascular compression, consistent with pain in areas innervated by the second branch of the trigeminal nerve. Genetic analysis as part of a phase 2 clinical study in patients with TN conducted by Convergence Pharmaceuticals Ltd revealed a previously undescribed de novo missense mutation in NaV1.6 (c.A406G; p.Met136Val). Whole-cell voltage-clamp recordings show that the Met136Val mutation significantly increases peak current density (1.5-fold) and resurgent current (1.6-fold) without altering gating properties. Current-clamp studies in trigeminal ganglia (TRG) neurons showed that Met136Val increased the fraction of high-firing neurons, lowered the current threshold and increased the frequency of evoked action potentials in response to graded stimuli. Our results demonstrate a novel NaV1.6 mutation in TN, and show that this mutation potentiates transient and resurgent sodium currents and leads to increased excitability in TRG neurons. We suggest that this gain-of-function NaV1.6 mutation may exacerbate the pathophysiology of vascular compression and contribute to TN.